Co-production in local government: process, codification and capacity building of new knowledge in collective reflection spaces. Workshops findings from a UK mixed methods study - Peter van der Graaf; Mandy Cheetham; Sam Redgate; Clare Humble; Ashley Adamson (BMC, 2021)
Abstract Background Co-production of research evidence is valued by local government to improve effective decision-making about public services in times of austerity. However, underlying structural issues of power (so-called 'dark shadows of co-production') challenge this ambition with limited evidence on how to embed research use sustainably. In this paper we reflect on mechanisms for increasing co-production in local government. Methods This paper presents findings from a Health Foundation funded research project that explored how a culture of evidence use to improve population health could be embedded in UK local government. Five linked work packages were undertaken using mixed methods. In this paper, we report the views of UK local authority staff who participated in four workshops (n = 54), informed by a rapid literature review and an online scoping survey. Results We identified five themes that facilitate public health evidence use in local government: (1) new governance arrangements to integrate national and local policies, (2) codifying research evidence through local system-wide approaches and (3) ongoing evaluation of programmes, and (4) overcoming political and cultural barriers by increasing absorptive capacity of Local Authorities to embed co-produced knowledge in their cognitive structures. This requires adaptive governance through relationship building between academic researchers and Local Authority staff and shared understanding of fragmented local policy making, which are supported by (5) collective spaces for reflection within local government. Conclusions Creating collective spaces for reflection in between government departments allows for iterative, interactive processes of co-production with external partners that support emergence of new governance structures to socially action the co-produced knowledge in context and build capacity for sustained evidence use.